2022
DOI: 10.3390/foods11111605
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sous Vide Parameters on Nutritional Characteristics and Safety of Pikeperch Fillets

Abstract: The aim of the study was to investigate the influence of temperature and time combination on the quality of pikeperch fillets and to propose settings which allow high nutritional quality fish fillets to be obtained. The material for the study consisted of 24 farmed pikeperch (Sander lucioperca) fillets, which were evaluated raw and after sous vide (SV) cooking proceeded at 65 °C for 45 min (SV65), 75 °C for 20 min (SV75), and 90 °C for 10 min (SV90). The chemical composition was affected by SV procedure; SV90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The analysis was carried out according to Modzelewska-Kapituła et al [ 21 ]. Immediately after sous-vide cooking, samples for sensory evaluation were prepared (dimensions approx.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was carried out according to Modzelewska-Kapituła et al [ 21 ]. Immediately after sous-vide cooking, samples for sensory evaluation were prepared (dimensions approx.…”
Section: Methodsmentioning
confidence: 99%
“…Four separate sessions of sensory evaluation were carried out; during each session, 6 samples were evaluated. Samples were evaluated using a 1 to 5 point scale, in terms of colour (from 5—homogeneous, typical, to 1—very inhomogeneous), aroma (from 5—typical, clearly perceptible, to 1—strong foreign), texture (from 5—firm, particularly tender, to 1—very soft or very hard, fibrous), juiciness (from 5—very juicy, to 1—very dry), and taste (from 5—desirable, typical, intense, no foreign aftertastes, to 1—atypical, strong foreign aftertaste) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The content of anserine in goose meat samples was determined using a component of the ChromQuest 5.0 Concentration Calculator program. Two replicates were prepared from each muscle, and two sub-samples of each extract were analysed by HPLC [19,23]. The limit of detection (LOD) and the limit of quantification (LOQ) of the method used were, respectively, 0.05 and 0.16.…”
Section: Anserine Content Determinationmentioning
confidence: 99%
“…Carnosine is identified in tissues where metabolic processes occur most effectively-the central nervous system, liver, kidneys, stomach and skeletal muscles [14,17]. The content of histidine dipeptides has been confirmed in beef [18,19], pork [20,21] and poultry [14,22] as well as in some fish and seafood [10,23]. Their content in tissues varies depending on the animal species, breed, sex, muscle activity and living conditions [10,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this Special Issue includes a paper focusing on the impact of three different combinations of sous vide (SV) on fatty acid composition, anserine and carnosine content, and sensory quality of pikeperch fillets (Sander lucioperca) [7]. The results showed that SV75 at 75 • C for 20 min and SV90 at 90 • C for 10 min are recommended for preparing pikeperch fillets, accounting for nutritional and safety aspects.…”
mentioning
confidence: 99%